Anti-Aging Activities of Asparagus Gel Ethanol Extract in Cosmetic Gel Agent for Facial Skin - Ginting, Henny Safrita; Fachrial, Edy; Lister, I Nyoman Ehrich; Amansyah, Adek (Majalah Kedokteran Bandung, 2021)
Asparagus is a vegetable that contains phenolic compounds with antioxidant properties that scavenges aging-triggering free radicals. This study aimed to investigate the components and anti-aging potentials of Ethanol Extract form Asparagus (EEA). The study was performed in February 2020 at the Pharmacy Laboratory, University of North Sumatera. The EEA was obtained through maceration using 96% ethanol. An antioxidant assay was performed and the total phenol and flavodoid content were determined using the spectroscopic method. Three gel formulas with different concentrations of EEA was prepared (F1: 1.5%, F2: 2.5%, and F3: 3.5%), and F0 was used as control. The parameters evaluated were moisture, oil content, texture, collagen, wrinkle, pigment, sensitivity, and pore. The result showed that asparagus had a moderate antioxidant activity (IC50: 118,992) with the total phenol and flavonoid contents of 15,9407 mg GAE/g and 3,2286 mg QE/g extract, respectively. The highest aging activities was seen in F3 (3.5%), followed by F2 (2.5%) and F1 (1.5%). The percentage of moisture, oil, texture, collagen, wrinkle, spot, sensitivity, and pore recovery were found to be 40.15%, 49.73%, 71.76%, 17.70%, 70.93%, 49.34%, 42.56% and 25.31%, respectively. Hence, it can be concluded that the EEA Gel at the highest concentration (3.5%) has a high content of phenol and flavonoid which can improve the skin moisture, oil content, texture, collagen, wrinkles, spots, sensitivity, and pores, which promotes anti-aging activities.